Impact of different front-of-pack nutrition labels on foods according to their nutritional quality: a comparative study in Mexico - Liliana Guadalupe Hernández-Nava; Manon Egnell; Carlos Alberto Aguilar-Salinas; José Ángel Córdova-Villalobos; Jorge Armando Barriguete-Meléndez; Simon Pettigrew; Serge Hercberg; Chantal Julia; Pilar Galán (Instituto Nacional de Salud Pública, 2019)
Objective. This study aimed to compare consumers' objec- tive understanding of five FoPLs [Health Star Rating system (HSR), Multiple Traffic Lights (MTL), Nutri-Score, Reference Intakes (RIs), Warning Symbol] in Mexico. Materials and methods. 1 001 Mexican consumers were recruited and asked to rank three sets of label-free products according to their nutritional quality, via a survey. Upon completion of this task, participants were randomized to one of five FoPL conditions and were again asked to rank the same sets of products, this time with a FoPL displayed on pack. Change in ability to correctly rank products across the two tasks was assessed by FoPL using ordinal logistic regression. Results. Nutri-Score and MTL performed best, followed Warning Symbol, HSR and RIs. Conclusion. Nutri-Score and MTL appear as efficient schemes to inform consumers on the nutritional quality of foods, in particular in Mexico, where it would be a helpful tool for consumers in purchasing situations.